2010
DOI: 10.1016/j.jneumeth.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Development of an apparatus and methodology for conducting functional magnetic resonance imaging (fMRI) with pharmacological stimuli in conscious rhesus monkeys

Abstract: Functional magnetic resonance imaging (fMRI) is a technique with significant potential to advance our understanding of multiple brain systems. However, when human subjects undergo fMRI studies they are typically conscious whereas pre-clinical fMRI studies typically utilize anesthesia, which complicates comparisons across studies. Therefore, we have developed an apparatus suitable for imaging conscious rhesus monkeys. In order to minimize subject stress and spatial motion, each subject was acclimated to the nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…The apparatus and animal habituation protocol have been described in detail previously (Murnane and Howell 2010). Scans were conducted in a Siemens (Siemens Healthcare, Erlangen, Germany) Trio 3 Tesla magnet.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The apparatus and animal habituation protocol have been described in detail previously (Murnane and Howell 2010). Scans were conducted in a Siemens (Siemens Healthcare, Erlangen, Germany) Trio 3 Tesla magnet.…”
Section: Methodsmentioning
confidence: 99%
“…Scans were conducted in a Siemens (Siemens Healthcare, Erlangen, Germany) Trio 3 Tesla magnet. The monkeys lay prone in a custom-built restraint cradle optimized for acquiring phMRI data from fully-conscious rhesus monkeys (Murnane and Howell 2010) and attached to a NHP head coil (RAPID MR International, LLC). Heart rate, oxygen saturation and expired gases were continuously monitored to ensure the safety of the animals inside the scanner.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over a period of at least 6 years starting in early adulthood, all three subjects engaged in daily cocaine self-administration with no planned periods of extended abstinence. Drug histories were complex and varied across subjects as reported in published studies for RMv-3 (Kimmel et al 2008; Lindsey et al 2004; Murnane and Howell 2010; Wilcox et al 2002), RRg-4 (Howell et al 2001; Howell et al 2002; Kimmel et al 2008) and RBp-3 (Banks et al 2009; Howell et al 2006; Murnane and Howell 2010). Based on self-administration protocols used in these studies and the duration of study assignments, each subject consumed > 10 g of cocaine.…”
Section: Methodsmentioning
confidence: 99%
“…This result aligns well with observations reported in human subjects. Methods have also been developed that enable rhesus monkeys to undergo MRI scanning without the use of anesthesia and with minimal restraint stress (Murnane and Howell, 2010). A recent study has shown that awake rhesus monkeys display ketamine-induced BOLD activation (Maltbie et al, 2016) that corresponds closely in both magnitude and extent to what has been reported in humans (De Simoni et al, 2013; Deakin et al, 2008; Doyle et al, 2013).…”
Section: Pharmacological Imaging and The Behavioral Effects Of Ketaminementioning
confidence: 99%